Sequential Au/Cu catalysis: a two catalyst one-pot protocol for the enantioselective synthesis of oxazole α-hydroxy esters via intramolecular cyclization/intermolecular Alder-ene Reaction - Nalivela, Kumara Swamy; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2018)
A convenient protocol for the enantioselective synthesis of oxazole α-hydroxy ester derivatives 4 from readily available propargylamides 1 and alkylglyoxylates 3 was developed. The first step of the one-pot procedure is the selective intramolecular in situ formation of an alkylideneoxazoline 2, which then in an intermolecular reaction is enantioselectively transformed to the oxazole α-hydroxy ester derivatives 4 in quantitative yield and good to excellent enantioselectivity via an asymmetric copper(II)-catalyzed Alder-ene reaction.
Gesehen am 29.08.2018